LIGHTWEIGHT DESIGN OF A COMMERCIAL VEHICLE FRONT AXLE BASED ON SECONDARY OPTIMIZATION - MA ChaoFan; ZHAO LiHui; YANG ZhenYi; FENG JinZhi; ZHENG SongLin (Jixie qiangdu)
A lightweight design method based on the idea of secondary optimization was proposed for a certain commercial vehicle front axle.The finite element model of the front axle was established and simulated.Combined with the fatigue endurance test,the true load of the front axle was investigated to verify the accuracy of the finite element model.The static tensile load and bending fatigue test of the real material of the front axle are taken as the light weight reference for obtaining the mechanical performance index of the front axle material after heat treatment.The overall model of the front axle is optimized and secondary optimization based on the mechanical model to ensure that the structure of the front axle meets the requirements of strength,stiffness and service life while achieving a lightweight design.The final total mass reduced 5.7 kg,to achieve the purpose of lightweight design.